Parallax of Antiquity. «Orgies» by Dmitry Gutov - Ovchinnikov, Mikhail V. (Actual Problems of Theory and History of Art, 2015)
The article focuses on the works of the established Moscow artist Dmitry Gutov in their relation to ancient cultural heritage. In 2012–2013 Gutov created a series of his objects-paintings made from iron bars wedged together. The artist uses an original and deliberately brutal technique in orderto recreate scenes of Greek vase painting and “ancient” drawings by Picasso. These artworks raise a number of questions about the place of antiquity in contemporary art, as well as the position of the contemporary artist in relation to classical heritage. The author of the article concludes that Gutov manages to fill his interpretation of ancient works with actual meanings and thus to prove the right of the contemporary avant-garde artist to work in the field of classical art.
Keywords: avant-garde; Dmitry Gutov; antiquity; contemporary art; interpetation